Advances in Austrian economics. Vol. 4 - Horwitz, Peter J.; Boettke, Steven (Emerald, 1997)
Part 1. Symposium on Austrian Macroeconomics. The economics of time and money: an introduction to a symposium on Austrian macroeconomics (S. Horwitz). Austrian and monetarist business cycle theories: substitutes or complements? (L.J. Sechrest). The theory of business fluctuations: new Keynesians, old monetarists, and Austrians (P.J. Shah). Capital and time: variations on a Hicksian theme (P. Lewin). Toward an Austrian theory of expectations (W.N. Butos). The regulation of bank capital adequacy (K. Dowd). Part II. Symposium on the Crisis of Economic Theory. The crisis of vision in modern economic thought: a symposium (P.J. Boettke). The crisis of vision in modern economic thought: some questions from the left (A. Callari). Beyond science: the economists' enterprise (J.M. Buchanan). The problem of vision in economics: a review essay (W. Samuels). The crisis of vision in modern economic thought: an Austrian economist's perspective (I.M. Kirzner). Part III. Current Research. Adolph Lowe and the Austrians (M. Forstater). Austrian insights and the theory of the firm (N. Foss). Francis Newman and the Austrian critique of socialism (J. Shearmur). Part IV. Review Essays. Lachmann's plan, and its lesson: comment on Lavoie (D.L. Prychitko). On regrouping the intellectual capital structure of Lachmann's economics (D. Lavoie). The dangers that court Hermeneutics: rejoinder to Lavoie (D.L. Prychitko). How entrepreneurs learn: a review of David Harper's entrepreneurship and the market process (I. Pongracic). Part V. Book Reviews. U. Maki, B. Gustafsson, and Knudsen, Eds.,. Rationality institutions and economic methodology (R. Koppl).
Keywords: Austrian school of economics.; elektronické knihy; electronic books